Couplings with variable characteristics of vehicles - Spruogis, Brosnislovas; Jakštas, Arūnas (Transport, 2005)
Couplings abruptly changing their torsional rigidity and carrying capacity when the transmitted torque reaches a particular value are considered. This state is achieved either changing the conditions of the deformation of a flexible member or by excluding it from torque transmission. In the presented paper the conditions of mode variation are determined and some relationships for determining major parameters of couplings are given.First Published Online: 27 Oct 2010